Analysis of the Maritime Conflict between Chile and Peru - Muhammad Rizqy Trirahardjo; Sifa Aulia Harits; Lantera Adeel Oase; Farid Putra Rachmansyah; Clara sophia naomi (International Journal of Law and Legal Ethics, 2023)
This study aims to analyze the results of the Peruvian and Chilean international disputes that have been submitted to the International Court of Justice (ICJ). The method used in this study is a descriptive method with a qualitative approach that is descriptive analysis. The method of approach used is qualitative. Qualitative methods are used to obtain in-depth data, data that contains meaning. The subjects in the dispute of this case are the States of Chile and Peru, where the object in question relates to the ownership of the maritime territorial boundaries of the two countries. The dispute that occurred between Chile and Peru regarding the border area resulted in a unilateral ownership claim of the territory and resulted in the signing of various agreements relating to the provisions in the form of norms in the international maritime direction The settlement of cases covering relations with countries is through the ICJ. It is stated that Peru and Chile will abide by any outcome of the provisions of the ICJ. This study deals with international relations as well as how to resolve border disputes according to applicable international law. This study is also a lesson for learners who are studying international relation